HUBUNGAN ANTARA PRESTASI BELAJAR DAN TINGKAT KECEMASAN MATEMATIKA PADA MAHASISWA CALON GURU SD/MI - Ifada Novikasari (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2016)
Mathematics anxiety has been recognized as a feeling depressed and anxious when it deals with the manipulation of numbers and mathematical problem solving in the real life and the academic situations. The anxiety tend to occur in someone with low mathematical ability. That is, individuals with low mathematics anxiety more comfort to solve the problem than someone who has high anxiety. It is interesting to examine, because it will be proved whether there is a relationship between learning achievement and mathematics anxiety